Review of Ian Barnes and Pamela M. Barnes, The Enlarged European Union - Figueroa, Bruno (Revista Mexicana de Política Exterior, 2022)
Ian Barnes and Pamela M. Barnes, The Enlarged European Union, London, Longman, 1995, 419 pp.